2015
DOI: 10.3389/fmicb.2015.00369
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin modifies the expression of the agr system in multidrug-resistant Staphylococcus aureus clinical isolates

Abstract: Staphylococcus aureus is an opportunistic pathogen that colonizes human hosts and causes a wide variety of diseases. Two interacting regulatory systems called agr (accessory gene regulator) and sar (staphylococcal accessory regulator) are involved in the regulation of virulence factors. The aim of this study was to evaluate the effect of vancomycin on hld and spa gene expression during the exponential and post-exponential growth phases in multidrug-resistant (MDR) S. aureus.Methods: Antibiotic susceptibility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…7,11,[20][21][22] Regarding agr typing, group II was more frequent among MRSA isolates, as already seen in other analysis. 8,13 Its was also high among VT-MRSA and hVISA, being associated with reduced vancomycin susceptibility. 12,23,24 Many VISA are highly enriched for the agr group II.…”
Section: Population Analysis Profile -Area Under the Curve Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,[20][21][22] Regarding agr typing, group II was more frequent among MRSA isolates, as already seen in other analysis. 8,13 Its was also high among VT-MRSA and hVISA, being associated with reduced vancomycin susceptibility. 12,23,24 Many VISA are highly enriched for the agr group II.…”
Section: Population Analysis Profile -Area Under the Curve Methodsmentioning
confidence: 99%
“…7 Additionally, this reduced vancomycin suscepti-bility is associated with dysfunction in the accessory gene regulator (agr) locus, a quorum sensing system that controls the expression of genes encoding virulence factors. 12,13 In this context, to understand the epidemiology and some molecular characteristics of MRSA with reduced vancomycin susceptibility is required to assist in the antimicrobial therapy and control the spread of these multiresistant microorganism. This study was designed to determine the prevalence of SCCmec and agr types among MRSA isolates, and to evaluate the association of these molecular characteristics with reduced susceptibility to vancomycin.…”
Section: Introductionmentioning
confidence: 99%
“…Early microarray analysis revealed that during the formation of E. coli biofilms and subsequent colonization, 38% of genes were modified, resulting in the altered expression of 600 genes (176). Similar to microarray analyses, quantitative real-time PCR (qPCR) examines a subset of genes from biofilm-isolated cells, while multiplex PCR detects multiple target sequences and is a useful tool for genetic analysis of polymicrobial/multispecies communities or gene polymorphisms (177)(178)(179) (Table 3). PCR product detection and quantification are based on probe chemistry.…”
Section: Quantitation and Viability Assaysmentioning
confidence: 99%
“…Subsequent to RNA extraction and purification, two assays are used to measure specific mRNA levels: Northern blotting and quantitative reverse transcription-PCR (qRT-PCR). Virulence determinants whose expression was explored by specific mRNA quantitation were hla (4,13,29,34,35,39,42), pvl (4,5,12,13,26), and spa (13,16,38,39,43); mRNA levels were normalized with respect to the expression of housekeeping genes, mostly the 16S rRNA gene or gyrB. Variation in mRNA levels may occur either by transcriptional modulation or by posttranscriptional mechanisms involving mRNA turnover.…”
Section: Readouts For Effects Of Antibiotics On Virulence Expressionmentioning
confidence: 99%